Determining the Risk Factors for Severe Acute Malnutrition among Children Aged 6-59 Months Admitted at Lubango Pediatric Hospital, Angola: A Case-Control Study - Ketha Francisco; Florence Kyallo; Peter Wanzala (Research Highlights in Disease and Health Research Vol. 1, 2023)
This chapter sought to determine the social demographic and clinical risk factors associated with severe acute malnutrition among children admitted at Lubango Pediatric Hospital, Angola. This was a case-control study in which cases were compared to age and gender-matched controls who were weighted for height. Data were gathered using a structured questionnaire administered by an interviewer, with carers serving as respondents: A trained clinician took the clinical history and examination, eliciting the duration of the illness and categorising symptoms such as fever and cough, among others. Anthropometric measurements were used to determine the child’s nutritional status. The caretakers and those who gave consent were counselled prior to the HIV test, and the child was tested for HIV antibodies using the Determine and Unigold HIV rapid tests, followed by post-test counselling for both HIV positive and negative children.Family order, HIV test results, previous history of admission with diarrhoea and malnutrition, duration of breast feeding, and the number of prior admissions were significant predictors of severe malnutrition. The burden of severe malnutrition among hospitalised children remains high. Breast feeding campaigns and family planning strategies must be strengthened. Furthermore, clinicians must be proactive in assessing the risk of malnutrition in HIV-positive children and children with recurrent admissions, particularly those with malnutrition and diarrhoea.